Pelatihan MC (Master of Ceremony) bagi Orang Muda Katolik (OMK) di Paroki Kristus Terang Dunia Waena Distrik Heram Kota Jayapura - Sitorus, Ferry Rhendra Pananda Putra; Lefaan, Avelinus (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
During the Covid-19 period there were many activities carried out using the internet network, including business, academic, office and religious activities. With so many activities using the internet network, these activities need people who have better public speaking skills, especially in religious activities. This condition makes the need to increase public speaking knowledge and skills through a master of ceremonies (MC) even more necessary. This is what is done at Paroki Kristus Terang Dunia Waena, especially for the congregation who are members of the Orang Muda Katolik (OMK). This training activity to improve public speaking through the master of ceremonies (MC) was carried out for one day in the hall of Paroki Kristus Terang Dunia Waena for thirty-five young congregation members who are members of the Orang Muda Katolik. Four training materials are provided as well as a question and answer room, group discussions and simulations. The simulation provided is to train the abilities of activity participants according to the objectives of the event being led, such as birthdays, weddings, graduations, official inaugurations and flag ceremonies. By carrying out this training activity, participants received material regarding public speaking through the master of ceremonies (MC), question and answer room, group discussions and simulations. Through discussions with the service team with trainers and local pastor, it is hoped that there will be a follow-up to this activity for coverage of activities in the Komunitas Basis (Kombas) of each participant in this training activity.